2017
DOI: 10.1155/2017/8526598
|View full text |Cite
|
Sign up to set email alerts
|

Sewage Sludge Amendment Combined with Green Manuring to a Coastal Mudflat Salt-Soil in Eastern China: Effects on Soil Physicochemical Properties and Maize Yield

Abstract: Sewage sludge and green manure have become widely used organic amendments to croplands in many regions of the world. However, the amending effect of the combination of sewage sludge with green manuring in reclaimed coastal mudflat salt-soil has been unclear yet. This paper was one of earlier studies to investigate and evaluate the effects of sewage sludge amendment combined with green manuring on selected soil physicochemical properties of the mudflat soil in a rain-fed agroecosystem. The mudflat salt-soil was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The findings of the current study are in line with previous reports. For example, Bai et al. (2017) observed that a combined application of sewage sludge and green manuring significantly elevated organic carbon content by 97.5–122.2%, 167.9–205.7%, 320.2–345.2%, and 352.8–427.8% at the rate of 30, 75, 150, and 300 t ha −1 in 2013 and 2014 seasons, respectively as compared to the control plots.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the current study are in line with previous reports. For example, Bai et al. (2017) observed that a combined application of sewage sludge and green manuring significantly elevated organic carbon content by 97.5–122.2%, 167.9–205.7%, 320.2–345.2%, and 352.8–427.8% at the rate of 30, 75, 150, and 300 t ha −1 in 2013 and 2014 seasons, respectively as compared to the control plots.…”
Section: Resultsmentioning
confidence: 99%
“…This was consistent with our previous studies that found sewage sludge has significant effects on soil alkalinity, salinity, and nutrient retention [ 14 , 23 , 24 , 48 ]. Specifically, soil pH was significantly lower in sewage sludge-amended soils as compared to CK treatment ( Table 1 ), which might be partially attributed to neutralization caused by lower-pH sewage sludge (6.32, Table S1 ) and organic acids (i.e., humic and fulvic acids) generated during the degradation of organic matters in sewage sludge [ 6 , 49 ]. Additionally, cumulative H+ secreted by plants roots and increased CO 2 , NO 3 − , and NO 2 − levels [ 50 , 51 , 52 , 53 ] might also be responsible for the decline in mudflat soil pH.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, considerably increased soil organic carbon content and decreased soil salinity were observed in sewage sludge-amended treatments as compared to unamended soil ( Table 1 ). The reason lies in the fact that applying sewage sludge with abundant organic matter into mudflat salt-affected soil can not only rapidly elevate soil organic carbon stocks [ 54 ], but also significantly facilitate water-stable aggregate formation, which efficiently prevents saline water from moving upward through soil capillaries, and finally reduced salt in the plough layer [ 6 ]. Apart from the soil organic carbon, sewage sludge application also promoted nitrogen and phosphorus contents in mudflat soil, which increased with the application rate of sewage sludge ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saline soils are diverse in nature and require specific strategies, such as the application of sulfurcontaining compounds to aid the management and reclamation for long-term productivity (Bello et al, 2021, Tomaz et al, 2020. Other related amendments such as sewage sludge, biochar, compost of municipal solid wastes and zeolite have also been used to reclaim sodic soils (Bai et al, 2017, Mukhopadhyay et al, 2021.…”
Section: Soil Improvementmentioning
confidence: 99%